2021
DOI: 10.1186/s12887-021-02637-9
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of comorbidities in school-aged children with cerebral palsy in Cross River State, Nigeria

Abstract: Background To describe the pattern of comorbidities in school-aged children with cerebral palsy (CP) and to identify which, if any, were associated with poor school attendance. A cross-sectional study, using the key informant methodology, between December 2017 and July 2018 was conducted in Cross River State, Nigeria. Assessments, confirmation of CP and identification of systemic comorbidities using standard tools and questionnaires were performed. Children confirmed to have CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Out of sixteen studies in this review, five were from Nigeria 19 , 21 , 23 , 25 , 26 ,, three were from Ghana), two studies were from Uganda 22 , 28 , and the remaining seven studies were from Kenya 30 , Sudan 20 , Cameroon 29 , Tanzania 33 , Botswana 27 , and Zambia 31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of sixteen studies in this review, five were from Nigeria 19 , 21 , 23 , 25 , 26 ,, three were from Ghana), two studies were from Uganda 22 , 28 , and the remaining seven studies were from Kenya 30 , Sudan 20 , Cameroon 29 , Tanzania 33 , Botswana 27 , and Zambia 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The review found that the highest proportion of malnutrition among children with cerebral palsy was 90% 22 , while the lowest proportion was 37.3% 23 . The sample sizes varied significantly, with the largest study including 388 participants from Nigeria 25 , and the smallest study including only 16 participants from Zambia 31 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…14 penelitian lain juga menyebutkan pada CP Spastik 70% mengalami masalah bicara 85%, kesulitan makan 86%, gangguan menelan 77%, disabilitas inttelektual 88%, gangguan aktifitas 62%, gangguan visual 54%, gangguan berkomunikasi 45%, epilepsy 35%, gangguan pendengaran 12% dan masalah nutrisi 51%. 15…”
Section: Diskusiunclassified
“…Owing to a variety of risk factors, many chronic diseases can start in childhood for individuals with cerebral palsy. Studies have reported on the prevalence of chronic and co-existing conditions among children with cerebral palsy, advancing knowledge of the extent and breadth of medical complexity for this pediatric population ( Berry et al, 2018 , Venkateswaran and Shevell, 2008 , Murphy et al, 2006 , Brooks et al, 2011 , Duke et al, 2021 , Reyes et al, 2019 ). However, many of these studies did not examine chronic diseases that are typically associated with aging.…”
Section: Introductionmentioning
confidence: 99%